2016
DOI: 10.1002/jat.3327
|View full text |Cite
|
Sign up to set email alerts
|

A 28‐year observational study of urinary cadmium and β2‐microglobulin concentrations in inhabitants in cadmium‐polluted areas in Japan

Abstract: The biological half-life of cadmium (Cd) is as long as 10-30 years. Exposure to this element induces renal tubular dysfunction, which is considered irreversible. β -microglobulin (β -MG) is a low-molecular-weight protein, and urinary β -MG is one of the most useful and critical indicators for the early detection of renal tubular dysfunction. However, very little research has been published concerning the long-term observation of Cd-induced adverse health effects. As such, this follow-up study was conducted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In addition, some researchers have revealed higher blood levels of manganese, copper, arsenic, cadmium and selenium in females than males ( 38 40 ). Similar to hair and blood, higher levels of urinary cadmium in females than in males was shown ( 33 ). On the other hand, some studies on children have reported lower blood levels of lead in girls than in boys ( 32 , 34 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, some researchers have revealed higher blood levels of manganese, copper, arsenic, cadmium and selenium in females than males ( 38 40 ). Similar to hair and blood, higher levels of urinary cadmium in females than in males was shown ( 33 ). On the other hand, some studies on children have reported lower blood levels of lead in girls than in boys ( 32 , 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…The current study results showed higher levels of some metals in girls’ than boys’ hair. Previous studies have reported accumulation of metals related to participants’ gender ( 33 – 36 ). For example, studies in Iran and Italy have reported higher level of scalp hair elements (i.e., lead, cobalt, cadmium, copper, and zinc) in girls than in boys ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically ascertaining threshold concentrations of UCd is greatly important and aids understanding of the health risks. Sensitivity indexes for the UCd burden have been a topic of wide concerned [ 15 , 21 ]. In response to our questionnaire, more than 50% of respondents indicated their awareness of suffering high Cd exposure for a certain time.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term Cd exposure has been reported, and renal dysfunction has already been proven [ 45 , 46 ]. Uβ 2 -MG and UNAG are in use as biomarkers for clinical diagnosis [ 15 , 21 ] and animal experiments [ 47 , 48 ]. In the later stages of Cd-induced renal injury, the tubular epithelial cells may shrink, fall off, and even disappear, and the tissue source of UNAG is lost [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation